2001
DOI: 10.21236/ada389225
|View full text |Cite
|
Sign up to set email alerts
|

Obscurants for Infrared Countermeasures III

Abstract: Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden, to Washington Headquarters Services, Directorate for Information Operations and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
2
3
0
Order By: Relevance
“…And because of their relatively small packing density (< 0.8 g/cm 3 ), the numerical values of σ v were even smaller than those of σ m . This agrees with the experimental results of Owrutsky et al (2001); measured extinction coefficients of metal oxide particles, including titanium oxide, aluminum oxide and manganese oxide were relatively small. It should be noted, however, that NanoActive® TiO 2 had a relatively high σ m value in the 3-to 5-m waveband.…”
Section: Effect Of Particle Size Distribution and Concentrationsupporting
confidence: 91%
See 2 more Smart Citations
“…And because of their relatively small packing density (< 0.8 g/cm 3 ), the numerical values of σ v were even smaller than those of σ m . This agrees with the experimental results of Owrutsky et al (2001); measured extinction coefficients of metal oxide particles, including titanium oxide, aluminum oxide and manganese oxide were relatively small. It should be noted, however, that NanoActive® TiO 2 had a relatively high σ m value in the 3-to 5-m waveband.…”
Section: Effect Of Particle Size Distribution and Concentrationsupporting
confidence: 91%
“…The reference particles (i.e., brass flakes, graphite flakes and carbon black) showed nearly constant values of σ m throughout the 3-to 12-μm wavelength range ( Figure 5), a trend similar to those observed in previous studies [Owrutsky et. al.…”
Section: Mass Extinction Coefficientssupporting
confidence: 87%
See 1 more Smart Citation
“…19,21,24 VER have been studied both theoretically [25][26][27][28][29][30][31][32][33][34] and experimentally, where nonlinear techniques, such as IR pump Raman probe and 2D IR, have provided great insights into the rates of VER, direction of heat flow, and diffusive/ballistic transport. 19,21,[35][36][37][38][39][40][41][42] Despite the vast knowledge acquired from such studies, the overall process of VER still remains challenging to understand. The ambiguity in VER, in particular IVR, arises because the energy transfer occurs from one bright mode to another mode via multiple dark states.…”
Section: Introductionmentioning
confidence: 99%
“…H.R.Carlon [1] showed that diesel oil can be changed into a white cloud that is particularly capable of shielding the visible light. J.C. Owrutsky etc [2] measured mass extinction coefficients of 18 candidates in both 3~5 μm and 8~12 μm bands and graphite is regarded as the best. However, it is difficult to attenuate effectively both visible and infrared radiation by using only one obscurant material.…”
Section: Introductionmentioning
confidence: 99%